Industry and business in Japan / edited by Kazuo Sato - Kazuo Sato (ed.) (London, 1980)
This volume gathers twelve essays written by Japan's leading experts on japanese industrial organization. All but two of the essays appeared originally in Japanese in Japanese economic journals and books. Eight of them were translated and published in japanese Economic Studies, a quarterly translation journal under my editorship. For reasons of space, some of these versions have been abridged. Two essays (Nos. 1 and 12) have been translated into English for the present volume, and two essays (Nos.2 and 3), already available in English, are reprinted.
Keywords: "Industrial organization Japan addresses, essays, lecture"